Knowledge, attitudes and perceptions of HIV and AIDS by rural South African secondary school learners - Muthivhi, Elelwani; Sodi, Tholene; Maunganidze, Levison; Mudhovozi, Pilot (Routledge, 2021)
We investigated the knowledge, attitudes and perceptions of secondary school learners (Grade 10 to 12) towards HIV/AIDS. Two hundred learners attending two rural village schools were participants (males =106, females =94, mean age = 16.5 years, SD = 2.4). Data were on their knowledge, attitudes and perceptions (KAPS) were collected using the adapted version of the MRC (2008) and WHO (1990) KAP Survey questionnaires on HIV and AIDS. Descriptive statistics were used to analyse the data. Results showed that participants got most information about HIV/AIDS from radio and television, with the internet, magazines, and newspapers being less popular sources of information. They also considered sharing injection needles with an HIV positive person and unprotected sex to be the two main sources of HIV transmission. Participants' attitudes towards HIV/AIDS were generally positive.